If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -6x = 4x + -8 Reorder the terms: 17 + -6x = -8 + 4x Solving 17 + -6x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 17 + -6x + -4x = -8 + 4x + -4x Combine like terms: -6x + -4x = -10x 17 + -10x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 17 + -10x = -8 + 0 17 + -10x = -8 Add '-17' to each side of the equation. 17 + -17 + -10x = -8 + -17 Combine like terms: 17 + -17 = 0 0 + -10x = -8 + -17 -10x = -8 + -17 Combine like terms: -8 + -17 = -25 -10x = -25 Divide each side by '-10'. x = 2.5 Simplifying x = 2.5
| 9-5k+2k=k-23 | | x^2+4x-1=9x-5 | | 6x+30=13-33 | | x^2+8x-2=7 | | x^2-(a+2b)x+b^2+ab=0 | | 24a=36 | | 12-x=30-4x | | 3x+4=5x-16 | | x^2+32x-196=0 | | x-17=6x+8 | | 9x-5=x+19 | | 9x+6=6x+10 | | 7x-20=04-3x | | 7(2x-5)=42 | | 21-7x=10+4x | | x+2=-3x+30 | | (5x-3)*2+(2x+1)*2=34 | | .4x=-5.3 | | 2x+12=4x+2 | | 10-8=30-15x | | 5x+4y+5z-2x+2z-6y= | | 6x+36=8x+20 | | (x+1)*(2x-6)=0 | | 285-4x=41x+20 | | -15+x=x+18 | | 10-7x=170-35x | | 149-7x=20x+20 | | a-6=-21 | | x^2-2x+13=10x-7 | | -3x+21=7x-9 | | 9x-15=2x+34 | | 2x+12=6x-24 |